Divided Cities. - Scholar, Richard (Oxford Amnesty Lectures 2003., 2006)
Based on the influential Oxford Amnesty Lectures, this volume examines the forces shaping urbanization today and the divisions that threaten the world's cities. It consists of essays by eight leading urban thinkers and practitioners. Many contemporary issues are addressed, including the impact of globalization and migration on cities, the consequences of the 'war on terror' for urban policing tactics, the new development paradigm being adopted by international institutions in the. developing world, the challenges facing urban planners in the developed world, and the suffering of the homeless.